On invariant sets of differential equations with impulses - Tkachenko, V. I. (Нелінійні коливання, 1999)
For a system of ordinary differential equations depending on a small parameter, defined on the direct product of a torus and aEuclidean space, and subjected to impulsive action on a submanifold of codimension 1 of the torus, we study the problem of existence of a piecewise smooth invariant set. Вивчається задача iснування кусково-гладкої iнварiантної множини системи диференцiальних рiвнянь, залежних вiд малого параметра та заданих на прямому добутку тора та евклiдового простору з iмпульсною дiєю на пiдмноговидi тора корозмiрностi 1.